Pengukuran Kinerja Perbankan Syariah di Indonesia dan Malaysia dengan Pendekatan Shariah Maqashid Index (SMI) Tahun Pelaporan Keuangan 2013-2017 - Anny Widiasmara; Wulan Retnowati (FEB Universitas Sultan Ageng Tirtayasa, 2020)
This research was conducted using the analysis of the concept of sharia maqashid index with an empirical study approach. The object of this study is Islamic banking in the Southeast Asian region, especially Indonesia and Malaysia. The results obtained from this study are the Malaysian Islamic Commercial Banks and the Indonesian Sharia Banking System still have an average performance value above Malaysia. This was obtained from the results of the assessment with maqashid shariah index and the SAW (Simple Additive Weigting) method that the majority Islamic Commercial Banks in Indonesia had the best performance at 46.22% banks, while the majority Islamic Commercial Banks in Malaysia amounted to 43.15% banks. However, from the total assessment of all performance indicators it was found that all assessment results per year and all performance indicators obtained showed that the financial performance of the Malaysian Islamic Commercial Banks was better overall with an average total rating of 1.348354 points while the total average value of the Indonesia Islamic Commercial Banks is 0.63564 points.